Correlation analysis of the rates of solvolysis of 4-bromopiperidine: A reaction following a Grob fragmentation pathway - Kevill, Dennis Neil; Ryu, Zoon Ha; D’Souza, Malcolm John (European Journal of Chemistry, 2017)
A Grunwald-Winstein treatment of the specific rates of solvolysis of 4-bromopiperidine gives for aqueous ethanol, methanol, acetone, and dioxane a very good logarithmic correlation against the YBr solvent ionizing power values with a slope (m value) of 0.46±0.02, consistent with the operation of a synchronous Grob fragmentation mechanism. When the organic component of the solvent is 2,2,2-trifluoroethanol (TFE), the data points show a negative deviation, consistent with an appreciable deactivating interaction of the acidic TFE component of the solvent with the lone-pair of electrons present on the nitrogen.